代际财富传承视角下城中村女性土地权维护动因研究——以中国广西南宁市两个城中村为例 - Yuan Xu (Sinolingua: Journal of Chinese Studies, 2025)
From the intergenerational wealth transfer perspective, this study explores motivations and practical significance of women’s land rights protection in Nanning’s (Guangxi, China) urban villages. Empirical research on Xingxing and Guanguan Villages shows traditional gender norms and institutional exclusion in village rules restrict married women’s land inheritance rights. Besides, "sonless families" see gender-discriminatory policy implementation, and migrant brides/sons-in-law face unequal rights allocation. The study reveals land rights are not just economic assets but core for intergenerational wealth transmission. Women use legal litigation, identity strategies and public advocacy to defend rights, essentially challenging the patriarchal structure. It also finds depriving women of land rights worsens poverty intergenerational transmission ("mothers’ poverty weakens sons’ prospects"). Based on relevant theories, it proposes revising the Law of the People’s Republic of China on Rural Collective Economic Organizations, setting up village rule review mechanisms and promoting gender equality awareness, to support a fair land rights protection system amid urban-rural integration.